Effects of digitally delivered mindfulness-based interventions in reducing burnout in healthcare workers: a systematic review and meta-analysis of randomized controlled trials - Riu, Silvia Dewi Mayasari; Hadi, Muhammad; Talibo, Norman Alfiat; Taplo, Yusti Muzdalifah; Tonapa, Santo Imanuel (Jurnal Ners, 2026)
Introduction: This review aimed to synthesize the evidence on the effectiveness of dMBIs in reducing burnout, depression, and mindfulness among healthcare workers. Methods: A systematic review and meta-analysis of randomized controlled trials (RCTs) were conducted according to the PRISMA 2020 guidelines. Six databases were searched through June 25, 2025. Eligible studies evaluated dMBIs among healthcare workers with burnout as a primary or secondary outcome. Standardized mean differences (SMDs) were pooled using a random-effects model. The risk of bias was assessed using the Cochrane Risk of Bias tool, version 2.0. Results: Nine RCTs were included, with 1,603 participants contributing to the analyzable data. dMBIs reduced emotional exhaustion (SMD = −0.34; 95% CI: −0.60 to −0.07) and depersonalization (SMD = −0.31; 95% CI: −0.55 to −0.07), and increased personal accomplishment (SMD = 0.48; 95% CI: 0.16 to 0.80). The dMBIs also improved mindfulness (SMD = 0.44; 95% CI: 0.07 to 0.82) and reduced depressive symptoms (SMD = −0.20; 95% CI: −0.37 to −0.03). The heterogeneity was moderate to high, and most studies were at a high risk of bias. Conclusions: dMBIs may improve burnout, mindfulness, and depression in healthcare workers, and their flexible digital format may support their use in workplace wellness programmes. However, the heterogeneity was moderate to high, and most trials were at a high risk of bias; therefore, the findings should be interpreted cautiously. Further high-quality trials are needed to confirm these effects and to identify the best delivery formats and engagement strategies.